The politics of pay reforms in Ghana. - Ayee, J.R.A. (The African Finance & Economics Consult, 2016)
Public sector pay is a major fiscal policy challenge in most African countries. Accordingly, countries have implemented various approaches to develop a realistic and acceptable pay policy. Ghana is no exception to the trend. Succeeding governments undertook without much progress pay reforms and reviews aimed at improving public service salaries and managing the recurring canker of disparities, inequities and imbalances in the pay administration system. As a contribution to the continued search for cogent reasons to explain the poor implementation of the Single Spine Pay Policy (SSPP), this paper adopts a political economy approach that shows sensitivity to the fact that the implementation of the SSPP is inherently complex and political; it is not just a technical exercise or a public service problem and therefore needs to be linked to the political objectives of the government, the interests of the groups affected, including those of the political elite and unions and associations as well as the prevailing political environment. The paper also discusses some of the policy and institutional framework deficits that have hampered the smooth implementation of the SSPP, which will need urgent attention by the government and other stakeholders, notwithstanding some of the gains made.
Keywords: Ghana; Pay reforms; Politics; Single spine pay policy